Avaliação da eficiência de uma planta industrial de produção de hidrogênio verde de média escala - Silva, Edenizio Oliveira da (2024)
Green hydrogen (H2V), produced by the process of electrolysis from water and renewable energy, will play a prominent role in long-term planet decarbonization. H2V is considered a promising solution capable of driving the energy transition and reducing dependence on fossil fuels. H2V is seen as essential for the world to achieve net-zero carbon emissions by 2050. The production of H2V has the potential to provide flexibility to the electrical system through the provision of various differentiated services over time, such as regulation, balancing, operational reserve, and seasonal energy arbitrage. Flexibility services allow for smoother integration of intermitente energy sources, such as solar photovoltaic and wind, by converting electricity surpluses into H2 through electrolysis and producing electricity through a fuel cell or combustion engine. The potential use of H2V spans different sectors, including transportation, industry, and power system, demonstrating its importance for the emergence of a sustainable economy. The objective of this work is to evaluate the performance of a real industrial H2V production plant composed of a solar photovoltaic power plant with an installed capacity of about 3 MWp and an electrolyzer with a capacity of 1.2 MW. Understanding the overall efficiency and each stage of H2V production is fundamental for making more assertive decisions regarding the implementation and integration of H2V into the electrical grid. Additionally, the work analyzes the efficiency of electricity production from H2V through the use of a fuel cell, and gas turbine. Based on measurements, the efficiency values obtained for the stages of H2V production were: photovoltaic plant 22.06%, rectifiers 94.61% and PEM electrolyzer 73.67%. Furthermore, the loss value due to the integrated consumption of utilities demanded in the H2 production process, known as Balance of Plant (BoP), was calculated at 10.65%, with a specific consumption of 63.04 kWh/kg. The overall efficiency obtained for the H2V production system was 61.70%. The efficiency in the process of reconverting H2 into electricity, from burning the hydrogen gas in a gas turbine, 29.86% and for the hydrogen cell, 37.32%. In the context of developing the hydrogen economy, the study and evaluation of the efficiency of an industrial H2V production system aim to contribute to the development of more effective and sustainable solutions for green hydrogen production, thus driving the transition to a cleaner energy future.